The Rule of Disposal of Sexual Organs and Cells: (A Comparative Analytical Study) - Salih, Khalid Mohammed; Wadi, Sara Najmadin (Journal of Legal and Political Studies, 2023)
The advancements achieved by medical professionals in the contemporary era, particularly in the field of organ transplantation, have significantly expanded the scope of medical surgeries and procedures. Various motivations underlie these operations involving the disposal of sexual organs and cells, including the desire to conceive offspring when sexual organs fail, cosmetic purposes, economic factors, mood-related reasons such as gender reassignment, and health considerations, wherein doctors employ these procedures to address certain pathological conditions such as cloning and artificial insemination. This study aims to explore the connection between birth control and the disposal of sexual organs and cells, as these procedures can lead to lineage corruption and raise doubts regarding genetic inheritance, given that sexual glands carry the genetic traits of the donor. This research addresses two primary aspects: firstly, the regulation surrounding the disposal of organs and sexual cells, and secondly, the impact of such procedures on proportions.
Keywords: medical professionals; organ transplantation; medical surgeries; disposal of sexual organs; lineage corruption